Transitioning from a hierarchical product organization to an open platform organization: A Chinese case study - Jiao Luo; Andrew H. Van de Ven; Runtian Jing; Yuan Jiang (Journal of Organization Design, 2018)
Organizations around the world are designing new forms of organizing in order to deal with the challenges of advances in information technology and digitization that promote increases in customization and innovation in the face of global competition. This paper presents a case study examining the challenges experienced by a large multinational firm as it transforms from a hierarchical product organization to an open platform network organization. We show that (a) role confusion, (b) control imbalance, and (c) staffing mismatches are key challenges associated with organizational redesign. The main lessons drawn from this case are discussed.
Keywords: 650; Organization design; Corporate venture; Strategy and structure; Micro-enterprise; China